Peran Stakeholders Dalam Pengembangan Wisata Bahari di Pelabuhan Kota Pasuruan - Adawiyah, Robik Atul; Eprilianto, Deby Febriyan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The development of marine tourism at the Port of Pasuruan, carried out by stakeholders in this study, is based on collaboration between the government and state-owned enterprises (BUMN) as a means of equitable regional potential development. However, several issues remain in its implementation. The aim of this study is to examine the roles of stakeholders in the development of marine tourism based on five role dimensions (policy creator, coordinator, facilitator, implementor, and accelerator). This study uses a descriptive qualitative method with data collection through observation, interviews, and documentation, followed by data analysis using reduction, presentation, and conclusion drawing. The results of the study show that the development of marine tourism has made progress through the active roles of stakeholders. The Secretary of State (Sekda) and PT Pelindo play the role of policy creators, but the involvement of relevant OPDs (regional work units) needs to be strengthened through formal agreements (PKS) to avoid role imbalances. The coordination role performed by Sekda, Dishub, and PUPR needs to be improved, especially regarding accessibility and parking. The facilitation role carried out by Sekda, Dispora, and Pelindo includes training and providing facilities, although the front area of the port still requires infrastructure improvements. Dispora and other OPDs are active as implementors, but pedestrian facilities remain suboptimal. As accelerators, Sekda and Dispora have  succeeded in speeding up tourism promotion and education, although information dissemination is limited due to the low digital literacy of the local community. It is expected that the Pasuruan City Government will optimize the cooperation agreements to include all stakeholders, strengthen coordination among OPDs with clear technical regulations and task divisions, and improve facilities and promotional strategies, both digital and conventional, so that the development of marine tourism at the Port of Pasuruan can become more inclusive and sustainable.